2012
DOI: 10.1063/1.4764514
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulations of pressure-driven flows in microchannels using Navier–Maxwell slip boundary conditions

Abstract: We present lattice Boltzmann simulations of rarefied flows driven by pressure drops along two-dimensional microchannels. Rarefied effects lead to non-zero cross-channel velocities, and nonlinear variations in the pressure along the channel. Both effects are absent in flows driven by uniform body forces. We obtain second-order accuracy for the two components of velocity and the pressure relative to asymptotic solutions of the compressible Navier–Stokes equations with slip boundary conditions. Since the common l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 55 publications
(108 reference statements)
1
27
0
Order By: Relevance
“…In other words, one cannot accurately capture the Knudsen layer without resolving the endpoint singularities [32]. Thus one cannot hope to capture the Knudsen layer or its manifestation a priori by using the lattice Boltzmann equation [50][51][52][53] or similar schemes, which is a special case of the linearized BGKW equation in the diffusive limit [54] and is incapable to capture any Knudsen-number effects beyond the Navier-Stokes equations [55][56][57].…”
Section: Discussionmentioning
confidence: 96%
“…In other words, one cannot accurately capture the Knudsen layer without resolving the endpoint singularities [32]. Thus one cannot hope to capture the Knudsen layer or its manifestation a priori by using the lattice Boltzmann equation [50][51][52][53] or similar schemes, which is a special case of the linearized BGKW equation in the diffusive limit [54] and is incapable to capture any Knudsen-number effects beyond the Navier-Stokes equations [55][56][57].…”
Section: Discussionmentioning
confidence: 96%
“…The first two conditions (9.4a) and (9.4b) impose no-flux and no-slip boundary conditions, and the third boundary condition (9.4c) on the tangential stress has a natural physical interpretation, unlike the alternatives involving higher moments [5,6,75] …”
Section: Implementation Of a Body Forcementioning
confidence: 98%
“…We use the approach of Wagner and Yeomans [93] and Bennett [5,6,75] to impose boundary conditions on the hydrodynamic moments u x , u y , and Π xx ,…”
Section: Implementation Of a Body Forcementioning
confidence: 99%
“…The Knudsen boundary layers are usually considered in the context of the rarefied gas dynamics as boundary conditions for non-equilibrium flows [1]. A very comprehensive critical review on the efforts devoted to appropriate LBM boundary conditions can be found in works [2,3]. The objective of this work is quite different.…”
Section: Introductionmentioning
confidence: 98%